The evaluation of two eleventh-grade senior high school textbooks - Delpianus Piong; Ra. Hasti Robiasih (Journal of English Language and Pedagogy, 2020)
The objectives of this research are to (1) describe the appropriateness of two English textbooks for the eleventh graders of senior high school based on Mukundan’s criteria, and (2) describe the strengths and weaknesses of the textbooks. This research is categorized as evaluation research as it aims at evaluating the appropriateness of two English textbooks. The data were collected through document analysis and to make sure the validity and readability of the research, therefore the researcher includes one of senior high school English teachers as the interrater reliability. The objects of the research are two English textbooks; Pathway to English and Talk Active for the eleventh graders of senior high school. The research found out that both textbooks Pathway to English and Talk Active meet the criteria of a good textbook. PTE textbook fully meets 11 criteria out of 14 criteria based on Mukundan’s criteria; the book in relation to syllabus and curriculum, methodology, supplementary materials, general content, listening, speaking, reading, writing, vocabulary, grammar, and exercises. Meanwhile, TA textbook successfully fulfils 6 criteria out of 14 criteria based on Mukundan’s criteria; the book in relation to syllabus and curriculum, methodology, general content, writing, pronunciation and exercises. The results also reveal the strengths and weaknesses of each textbook. First, the PTE textbook has the strengths in the specification of the syllabus, various teaching-learning activities, activities address learning targets, supplementary material like a workbook and audio recording, teacher’s guide, simplicity and complexity of the tasks, tasks are supportive, appropriate listening tasks, the language use is authentic, speaking activities are designed to initiate students’ communicative practice and varied exercises. The weaknesses of PTE are the textbook does not provide pronunciation activity, the layout is less attractive, the price is expensive, it does not include various listening contexts such formal and informal contexts and also it has no a ready-made CD as support for listening skill. Meanwhile, the strengths of TA are the textbook is relevant to syllabus and curriculum, it provides workable activities which work well in most classroom situations, varied tasks which move from simple to complex, speaking activities are developed to improve students’ meaningful communication, reading texts are appropriate in length, writing tasks have achievable goals of improving students writing skills and the tasks are interesting, there is a number of new words across in each lesson, the textbook provides students with a glossary at the back of the textbook, pronunciation tasks are useful and interesting, exercises are adequate and they have clear instructions to understand. The main weakness of TA is that the textbook does not have an authentic audio recording or CD for listening skills, the listening activities are less appropriate and various listening contexts are not considered, individual, pairs and group work are not given in the same way in speaking practice, the price of the textbook is too expensive, it does not indicate efficient use of texts and visuals and overall, the textbook is less appropriate for the background knowledge and levels of students since it is provided balanced four basic language skills in it.